TIKTOK APPLICATION AS AN ENGLISH LEARNING MEDIA: STUDENTS’ PERCEPTION - Anugrah Ilham Sanusi; Muhammad Anjar Nugraha; Ida Maulida (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2023)
The TikTok application is a social media application that contains video content about anything, including some English learning content. English learning media is a tool or method used by teachers to make it easier for students to understand English subject matter, therefore this TikTok application was chosen as a learning Media. This study aims to determine students' perceptions of the use of the TikTok application as a medium for learning English and also to find out whether the TikTok application is used by students as an interesting and interactive media for learning English. The sample in this research was 139 eleventh-grade students of SMK PGRI Subang. This research design used qualitative research methods with a case study approach by getting the data from questionnaires and interviews. Questionnaires were used to determine students' perceptions of the TikTok application as their learning media in learning English, Interviews were used to determine the use of the TikTok application as an interesting and interactive media in learning English. The results show that the number of users of the TikTok application among students is 65.5%, the frequency of students using the TikTok application is 55.4%, the use of English learning media in the TikTok application for students provides a positive learning experience 64%, Using TikTok is easier for students to access video content that contains English, discusses vocabulary, speaking, grammar, which is easy for students to remember 45.3%, TikTok gives students the opportunity to hone their English skills 43.2%. Overall, it shows that the use of TikTok in learning English received a positive response from the majority of students, although there were some who were still doubtful. TikTok has had a positive impact on students in various aspects. The results of interviews regarding participant responses showed positive and varied views regarding the use of the TikTok application as an English learning media. Many participants found this experience enjoyable, beneficial, and improvement the understanding and knowledge of the language. The interactive and entertaining nature of TikTok content makes the learning process interesting and effective.